2012
DOI: 10.1039/c2dt30725a
|View full text |Cite
|
Sign up to set email alerts
|

Heteroleptic silver-containing ionic liquids

Abstract: MethodsAll chemicals purchased were of reagent grade and used without further purification.[Ag(MeCN)][Tf 2 N] was synthesised as previously described [S1]. TGA studies were performed on a TA instruments Q600 thermogravimeter. The temperature was scanned from room temperature up to 400 °C at a heating rate of 5 °C per minute. Elemental analyses (C, H, N) were carried out using a CE Instruments EA-1110 elemental analyser. The IR and Raman spectra were recorded on a Bruker Vertex 70 FTIR spectrometer, coupled wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
69
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(76 citation statements)
references
References 19 publications
7
69
0
Order By: Relevance
“…[8][9][10][11][12][13] Several examples of electrodepositiono fm etals from liquid metal salts can be found in the literature. [14][15][16][17][18][19][20][21][22] Our research group has obtainedv ery promising resultsf or the electrodeposition of copper, [23][24][25] silver, [26][27][28][29][30] palladium [31] and lithium. [32] Metal coatings of ag ood quality were achieved at very high current densities,e ven withoutt he use of additives.…”
Section: Introductionmentioning
confidence: 98%
“…[8][9][10][11][12][13] Several examples of electrodepositiono fm etals from liquid metal salts can be found in the literature. [14][15][16][17][18][19][20][21][22] Our research group has obtainedv ery promising resultsf or the electrodeposition of copper, [23][24][25] silver, [26][27][28][29][30] palladium [31] and lithium. [32] Metal coatings of ag ood quality were achieved at very high current densities,e ven withoutt he use of additives.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, in the ion pairs containing silver, the anion is involved in several HBs with the H atoms from both imidazole rings, in line with the X-ray structure of corresponding ILs. 22 As expected, relative to [Ag(mim) 2 ][Tf 2 N], more conformers were attained for the ion pairs [(C 2 im)Ag(mim)][Tf 2 N] and [(C 4 im)Ag(mim)][Tf 2 N], due to two different alkylimidazole ligands coordinated to silver center in the latter systems. In addition, all the N···H(C2) distances in the ion pairs containing silver are predicted longer than those in [C 1 mim][Tf 2 N], which implies weaker N··· H(C2) HBs in these ion pairs (see below).…”
Section: Resultsmentioning
confidence: 64%
“…The crystal structures and physicochemical properties of these TM-ILs have been reported in previous papers. 21,22,26,27 In addition, two conventional ILs, [C 1 mim][Tf 2 N] and [C 1 mim][BF 4 ], were also chosen for comparison. First, all possible conformations of the ion pairs for the studied TM-ILs were simulated, and different molecular interactions, such as hydrogen bonds (HBs) and electrostatic forces, between the cations and anions were examined.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Binnemans and Fransaer, [1][2][3][4] Huang and Dai 5 and their co-workers have demonstrated that silver ionic liquids, for example, are superior electrolytes for the electrodeposition of metallic silver with high current density. These metal ionic liquids possess advantages such as high solubility of metal salts and strong response to magnetic fields that much outperform common organic ionic liquids.…”
mentioning
confidence: 99%